Implementasi Kendali Dan Monitoring Sistem Proteksi Arus Listrik Pada Extension Kabel Berbasis Node-Red Sebagai Upaya Pencegahan Kebakaran - Habib Nur Syamsi Hidayat; Aditya Chandra Hermawan; Ayusta Lukita Wardani; Mahendra Widyartono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The unwise use of electrical energy in households can lead to energy wastage and pose risks such as short circuits, which may result in fires. This research developed a Node-Red-based protection system using an ESP8266 microcontroller and a PZEM 004-T sensor to detect voltage, current, and power in real-time. The system automatically disconnects the current when overload conditions are detected, especially on extension cables. Testing was conducted on household devices such as laptop chargers, fans, and soldering irons. Results demonstrate that the system can accurately monitor current and power, maintain electrical stability, and cut off electricity when the load exceeds the safe threshold, thus reducing fire risk. This implementation is expected to enhance household electrical safety and serve as a reference for further development in IoT-based protection systems.